2022
DOI: 10.1111/pcn.13342
|View full text |Cite
|
Sign up to set email alerts
|

Toward recovery in schizophrenia: Current concepts, findings, and future research directions

Abstract: Schizophrenia was initially defined as “dementia praecox” by E. Kraepelin, which implies progressive deterioration. However, recent studies have revealed that early effective intervention may lead to social and functional recovery in schizophrenia. In this review, we provide an overview of current concepts in schizophrenia and pathophysiological hypotheses. In addition, we present recent findings from clinical and basic research on schizophrenia. Recent neuroimaging and neurophysiological studies have consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 151 publications
0
38
0
Order By: Relevance
“…The experimental protocol developed here can be used in various neuroscientific studies on animals to provide fundamental insight into pathophysiology. Based on the findings from animal studies, new, effective eye tracking tests could be created for the early diagnosis of psychiatric disorders, including schizophrenia ( Onitsuka et al, 2022a ). In addition, research with non-human primates can suggest effective pharmacological manipulation strategies and targets, which can facilitate drug development and consequently contribute to psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocol developed here can be used in various neuroscientific studies on animals to provide fundamental insight into pathophysiology. Based on the findings from animal studies, new, effective eye tracking tests could be created for the early diagnosis of psychiatric disorders, including schizophrenia ( Onitsuka et al, 2022a ). In addition, research with non-human primates can suggest effective pharmacological manipulation strategies and targets, which can facilitate drug development and consequently contribute to psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, the consequences of burnout are not negligible because of the direct repercussions on the patient and the population: a decrease in the quality of care, an increase in medical errors, a decrease in caregiver productivity and patient satisfaction. 8 What happens when the roles are reversed, and the professional plays the role of the patient because of the physical and mental repercussions of burnout? It is unfortunate that decisions about mass offloading or closing rural emergency departments have to be made.…”
mentioning
confidence: 99%
“…7 Cognitive impairments in schizophrenia cause difficulty in solving daily life problems as well. 8 These factors may increase the risk of mask‐induced ear injuries in patients with schizophrenia. If the patient had lived alone and no one had checked regularly, the ear injuries might have been worse.…”
mentioning
confidence: 99%
“…Psychotic disorders, including schizophrenia, predominantly occur in late adolescence and early adulthood and can affect social functioning of patients throughout their lifetime ( 1 , 2 ). Given that patients with psychotic disorders exhibit diverse clinical courses, such as their clinical symptoms easily disappearing, fluctuating, or persisting without treatment response ( 3 ), psychotic disorders may be not a unitary disease but rather a heterogeneous collection of syndromes.…”
mentioning
confidence: 99%
“…Substantial biological research in psychotic disorders using molecular, neurophysiological, and neuroimaging measurements has demonstrated that neurobiological abnormalities are likely present at illness onset and before onset ( 4 10 ), and that distinct patterns of neurobiological changes are mixed within psychotic disorders ( 11 , 12 ). Such neurobiological heterogeneity may represent different subsequent clinical courses and functional outcomes ( 2 , 13 16 ).…”
mentioning
confidence: 99%